Cardiac myxoma embolic events: characterization and predictors. (3rd October 2022) - Lacerda Teixeira, B; Grazina, A; Castelo, A; Ferreira, V; Bras, P; Branco Mano, T; Gil, R; Moura Branco, L; Galrinho, A; Timoteo, A T; Rio, P; Pinto, E; et al.
Abstract: Introduction: Myxomas are the most common heart tumors. Although, myxomas are often diagnosed incidentally in asymptomatic patients, they are frequently associated with embolic events, becoming an important cause of morbidity and mortality. Whether some myxomas' characteristics predict more embolic risk is not well established. Objectives: This analysis aims to describe the clinical and echocardiographic data in a long cohort of patients with cardiac myxomas and to establish potential predictors of embolic events int these patients. Methods: Between 1990 and 2021, 88 patients were diagnosed with cardiac myxoma. 84 were included in this analysis. Baseline characteristics, echocardiographic findings and embolic events were noted retrospectively. A binary logistic regression analysis using SPSS statistics software, version 25.0 was performed to establish possible embolic predictors. Results: 84 patients (mean age 63.1±12.9 years old, 75% female) with cardiac myxoma (sporadic type in 100%) were analyzed (table 1). The majority were located in the left atrium (88.1%, n=74), followed by right atrium (10.7%, n=9) and right ventricle (1.2%, n=1). The average dimension (longer axis) was 36.8±17.4mm. 9.6% of the patients (n=8) had Atrial Fibrillation (AF) rhythm. 22.6% of the patients (n=19) experienced embolic events, the majority to the central nervous system (19.0%, n=6), followed by peripheric/limbs (2.4%, n=2), renal (1.2%, n=1) and coronary (1.2%, n=1). The presence of irregular borders (papillary, bosselated) was the only parameter independently associated with increased risk of embolic events, by 6 times (OR 6.78, 95% confidence interval of 2.14–21.51, p-value 0.001). Neither the presence of AF, myxoma dimensions, presence of calcifications, pediculated insertion, myxoma mobility or heterogeneous aspect predicted embolic events with statistical significance (table 2). Conclusions: Cardiac myxomas are frequently associated with embolic events (22.6% in our population), posing an important cause of morbidity and mortality in these patients. Besides the presence of irregular borders, the other myxoma's characteristics did not consistently predict the occurrence of embolic events. This data supports the well-recognized fact that all cardiac myxomas have the potential to embolic events, and therefore, should be excised, although those with very irregular borders are at much higher risk of embolization. Funding Acknowledgement: Type of funding sources: None.